Oxidação Eletroquímica de Anlodipino e Hidroclorotiazida Sobre o Eletrodo de Diamante Dopado com Boro: Potencialidade de Determinação Simultânea em Urina - Mansano, Guilherme Roberto; Sartori, Elen Romão (Orbital: The Electronic Journal of Chemistry, 2015)
The present study was undertaken to evaluate the use of boron-doped diamond The present study was undertaken to evaluate the use of boron-doped diamond electrode in the simultaneous voltammetric determination of antihypertensives amlodipine and hydrochlorothiazide in urine sample. Two very well-resolved and reproducible oxidation peaks of amlodipine and hydrochlorothiazide, with separation of 0.360 V, were obtained in Britton-Robinson buffer (pH 5.0). Under the optimum analytical experimental conditions, the square-wave voltammetric method exhibited linear responses for simultaneous determination of amlodipine and hydrochlorothiazide in the concentration range 1.0 × 10−7 – 2.1 × 10−6 mol L−1 and 2.0 × 10−6 – 2.2 × 10−5 mol L−1, with detection limits of 5.6 × 10−8 mol L−1 and 1.6 × 10−7 mol L−1, respectively. The proposed method was applied in the simultaneous determination of amlodipine and hydrochlorothiazide in urine sample. DOI: http://dx.doi.org/10.17807/orbital.v7i1.673